SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP BERBASIS WEB MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Arliyandi; Wendy Asswan Cahyadi; Suhendra Anjar Dinata (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
Continuously evolving technology influences consumer preferences in choosing a laptop, often faced with complex information and numerous choices. This study aims to develop and test a web-based decision support system using the Simple Additive Weighting (SAW) method, designed to assist consumers in selecting a laptop that suits their needs. Testing was conducted to measure the system's accuracy and efficiency in providing relevant recommendations. The results show that the system can provide accurate recommendations based on user preferences, supporting more personalized laptop selection decisions.